Effect of bromelain on ischemia-reperfusion injury in the torsion model created in polycystic and normal ovarian tissues - Ulusoy Tangul, Sevgi; Onat, Taylan; Aydoğan Kirmizi, Demet; Doganyigit, Zuleyha; Kaymak, Emin; Oflamaz, Aslı; Şenayli, Atilla; Somuncu, Salih (Frontiers in Pharmacology, 2025)
PurposeDue to its increased volume, polycystic ovarian tissue is more prone to torsion than normal ovarian tissue. In treating ovarian torsion, detorsion is applied to ensure oxygenation of hypoxic tissues. However, the resulting oxygen radicals cause tissue damage. Bromelain is a substance obtained from pineapple, and studies in the literature show it is used as an antioxidant. This study aimed to evaluate the damage caused by ischemia-reperfusion (I/R) in the torsion-detorsion model created in normal and polycystic ovarian tissue and investigate the role of bromelain in this damage.MethodsPolycystic ovarian tissue was created by applying dihydroepiandrosterone sulfate to rats. Afterward, a torsion-detorsion model was used for all rats. The rats were divided into six groups: the polycystic ovary sham-operated group (P-S), the normal ovary sham-operated group (N-S), the polycystic ovary ischemia/reperfusion group (P-IR), the normal ovary ischemia/reperfusion group (N-IR), the polycystic ovary ischemia/reperfusion group treated with bromelain (P-IRB), and the normal ovary ischemia/reperfusion group treated with bromelain (N-IRB). After the procedure, tissues were collected for histopathological examination, and MDA, TUNEL, and NF-κB levels were measured.ResultsThis study detected significant decreases in MDA and NF-κB levels and apoptotic cell numbers assessed by TUNEL staining in groups with IR damage and given bromelain compared to the control groups. The number of TUNEL-positive cells was found to be highest in the P-IR group (8.80 ± 2.98) and significantly lower in the bromelain-administered P-IRB (1.04 ± 1.09) and N-IRB (0.52 ± 0.58) groups (p< 0.05). NF-κB expression was also high in P-IR and N-IR groups, while it was significantly decreased in bromelain-treated groups (P-IRB and N-IRB) (p< 0.05). In addition, IR damage was more pronounced in polycystic ovary tissue than in normal ovary tissue.ConclusionIschemia perfusion damage may be more pronounced in polycystic ovarian tissue than in normal ovarian tissue. Bromelain may be preferred to prevent I/R injury caused by ovarian torsion. It is also thought that bromelain may function in treating polycystic ovaries, and further studies can be conducted on this subject.